Insights into Radiology Publications - Paul Sathiadoss; Rajesh Bhayana; Zara A. Shaikh; Satheesh Krishna (Indian Journal of Radiology and Imaging)
The evolution of modern medicine has been significantly driven by medical and health care research, underscoring the importance of disseminating findings to advance health care. Medical literature, encompassing various publication types such as case reports, review articles, and original research, plays a crucial role in this process by facilitating the communication and discussion of new discoveries. This review article provides a comprehensive guide to understanding and navigating radiologic publications. It examines the various types of radiologic research articles, including case reports and series, pictorial reviews, original research, systematic reviews, and meta-analyses, each of which serve distinct purposes in contributing to the field of radiology. The study adopts the “six honest men” approach—addressing why, who, what, when, where, and how—to elucidate the essential elements of successful radiology research and publication. Key topics include the motivations for publishing, the types of articles suited for different research questions, and strategic considerations for selecting appropriate journals. Additionally, the review highlights the importance of understanding publication timing, journal selection criteria, and the overall publication process, including manuscript preparation and peer review. By offering these insights, the review aims to equip early-career researchers with the knowledge and skills necessary to effectively contribute to radiology literature and advance their academic and professional careers.